The Duality of the MAPK Signaling Pathway in the Control of Metabolic Processes and Cellulase Production in Trichoderma reesei. Issue 1 (December 2018) - de Paula, Renato; Antoniêto, Amanda; Carraro, Cláudia; Lopes, Douglas; Persinoti, Gabriela; Peres, Nalu; Martinez-Rossi, Nilce; Silva-Rocha, Rafael; Silva, Roberto
Abstract In this study, through global transcriptional analysis by RNA-Sequencing, we identified the main changes in gene expression that occurred in two functional mutants of the MAPK genestmk1 andtmk2 inTrichoderma reesei during sugarcane bagasse degradation. We found that the proteins encoded by these genes regulated independent processes, sometimes in a cross-talk manner, to modulate gene expression inT. reesei . In the Δtmk2 strain, growth in sugarcane bagasse modulated the expression of genes involved in carbohydrate metabolism, cell growth and development, and G-protein-coupled receptor-mediated cell signaling. On the other hand, deletion oftmk1 led to decreased expression of the major genes for cellulases and xylanases. Furthermore, TMK1 found to be involved in the regulation of the expression of major facilitator superfamily transporters. Our results revealed that the MAPK signaling pathway inT. reesei regulates many important processes that allow the fungus to recognize, transport, and metabolize different carbon sources during plant cell wall degradation.